Evaluation of PT Pegadaian Syariah Financial Performance through the RGEC Approach in the Perspective of Islamic Economics - Hari Winarsa; Akbar, Firman Muhammad Abdurrohman (LP2M IAIN Palopo, 2025)
This study aims to evaluate the financial performance of the Sharia Business Unit (UUS) of PT Pegadaian (Persero), hereinafter referred to as PT Pegadaian Syariah, during the 2020-2024 period using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) approach and analyzing it from a Sharia economic perspective. The research method used is quantitative descriptive by utilizing secondary data from the annual report of PT Pegadaian (Persero) which presents UUS operational data for the 2020-2024 period. The results of the analysis show varying performance in each RGEC component. The Risk Profile, especially related to Non-Performing Financing (NPF), shows relatively good management, although liquidity challenges require attention given the characteristics of non-bank funding. The Good Corporate Governance (GCG) aspect qualitatively shows a commitment to Sharia principles, but requires strengthening in the transparency of specific UUS implementation. Earnings (Rentability) performance shows profit growth, but profitability ratios such as ROA and ROE, when using consolidated data as a proxy, need to be improved in terms of efficiency from the perspective of UUS asset management in particular. The Capital component shows a good level of health, supported by the capital strength of the parent entity. From a Sharia economic perspective, the operations of PT Pegadaian Syariah are in line with efforts to fulfill Maqasid al-Shariah, especially in the aspects of asset protection (hifdz al-maal) and community economic empowerment (hifdz al-nafs). However, optimizing the achievement of welfare and justice requires continuous evaluation of product structure and margins. This study underlines the importance of adapting the RGEC method for Sharia NBFIs and the need for deeper integration between financial performance assessments and the achievement of substantive goals of Sharia economics, beyond just normative health assessments.